Dividend Policy and Firm Performance: A Study of Selected Banks in Nigeria - Okoh, Johnson Ifeanyi; Oyeranmi, Akinloye O.; Amahi, Fidelis U.; Agbadua, Oyakhiromhe Bamidele; Nwajei, Isiekwene Michael (NIU Journal of Social Sciences; Vol 9 No 3 (2023): NIU Journal of Social Sciences, Vol. 9 No. 3, September 2023DO - 10.58709/niujss.v9i3.1712, 2023)
This study investigated how the dividend policy affected the performance of a few Nigerian banks. Secondary data from the annual statements of the selected banks for the years 2010 to 2021 were used in the study. The study was guided by relevant specific objectives and hypotheses which were to test for the long run effects of the dividend policy and consider the effects of other determinants of bank performance for the period under study.  The various preliminary tests and diagnostic tests were conducted to confirm that the data which was time series in nature were fit for empirical uses to avoid spurious results. The study utilized panel regression with the aid of E-views statistical package. The panel regression results indicates that the coefficient of the   variables DEPOSIT, ASSET and Dividend indicate positive signs and are significant statistically.  The positive coefficient of the variable DEPOSIT indicates that a percentage increase in the banks deposit increases the banks’ performance by 15%. For the variables ASSET and Dividend, the results show that a percentage increase in the bank’s asset and dividends increases the banks’ performance by 002% and 02% respectively. The results therefore confirmed that dividend policy by banks can enhance the overall performance of selected quoted Nigerian banks. Keywords : Dividend policy, firm performance, banks, Nigeria